Digital Literacy and Digital Competence among EFL Teachers: A Systematic Literature Review - Suhono Suhono; Bambang Yudi Cahyono; Evi Eliyanah; Maria Hidayati; Raga Driyan Pratama; Sahyoni Sahyoni; M. Hilmy Hidayatullah (Online Learning In Educational Research (OLER), 2025)
Research on digital literacy and digital competence in English teacher education has expanded substantially over the past decade, reflecting growing scholarly attention to teachers’ roles in digitally mediated learning environments. This study systematically maps publication trends, collaboration patterns, and thematic emphases in this research domain, identifying how digital literacy and digital competence are conceptualized and empirically addressed. A Systematic Literature Review (SLR) was conducted following the PRISMA framework, drawing on Scopus-indexed publications from 2015 to 2025. Bibliometric analysis examined publication growth, co-authorship networks, country contributions, and keyword co-occurrences, complemented by thematic synthesis to interpret conceptual and pedagogical patterns. VOSviewer was used to visualize bibliometric linkages. Findings indicate steady publication growth with limited international collaboration and regional concentration, particularly in Southeast Asia. Thematic synthesis reveals that digital literacy is commonly framed as foundational skills that include information access, communication, and basic technology use, while digital competence emphasizes pedagogical integration, professional development, and context-responsive teaching. Advanced aspects such as AI-supported pedagogy, critical digital engagement, and transformative digital practices remain less explored. Overall, both constructs are central in English teacher education but are addressed with varying conceptual depth.